(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2015)
Most of the intellectual property generated at universities is the result of research funded by the government. Ownership of intellectual property for government-funded research is originally vested in the government as the benefactor. However, the ownership status of intellectual property has been an impediment to the exploitation of the intellectual property generated at universities and thus has resulted in piles of unused intellectual property from research funded by the government. The implementation of the Bayh Dole Act 1980 by the United States has become a model for many countries whereby the act provides that ownership of intellectual property resulting from government-funded research is vested in the universities as an incentive to boost research and innovation in universities. This article discusses intellectual property ownership rules in Malaysia and then analyses ownership provisions under the Policy of Commercialization of Intellectual Property from R & D funded by the Government of Malaysia in 2009, and makes comparisons with the provisions under the Bayh Dole Act 1980. Implementation of laws relating to ownership of intellectual property from government-funded research is necessary in order to create uniformity for intellectual property rights in Malaysian universities and to ensure smooth process of intellectual property commercialization. Keywords: ownership, intellectual property, goverment-funded research, university